Vapor phase dealloying-driven synthesis of bulk nanoporous cobalt with a face-centered cubic structure. Issue 37 (2nd September 2021) - Shi, Yujun; Wang, Yu; Yang, Wanfeng; Qin, Jingyu; Bai, Qingguo; Zhang, Zhonghua
Abstract : The VPA–VPD strategy successfully realizes the fabrication of bulk nanoporous FCC-Co because of the temperature effect and size influence. Abstract : Cobalt (Co) mainly exists in two allotropic forms: a low temperature hexagonal close-packed (HCP) structure and a high temperature face-centered cubic (FCC) structure. However, annealing at high temperature only induces the formation of FCC-Co on the surface of a bulk sample and fabrication of bulk FCC-Co is still a great challenge. In this work, nanoporous FCC-Co with a macroscopic dimension is successfully fabricated via a vapor phase alloying (VPA)–vapor phase dealloying (VPD) strategy using zinc (Zn) as the vapor source. Moreover, the thickness of the nanoporous layer could be modulated by adjusting the VPA time. The bulk nanoporous FCC-Co with different shapes and sizes can be fabricated owing to the flexibility and reactivity of the Zn vapor. Both the temperature effect and the size influence contribute to the formation of bulk FCC-Co during the VPD process. In addition, nanoporous FCC-Co shows different magnetic properties as benchmarked with pristine HCP-Co. Our findings provide a new methodology for the preparation of bulk nanoporous FCC-Co which may exhibit unique properties and potential applications.